Orientation effect of arc array horizontal tubes inside a phase change storage unit on melting and solidification characteristics - Mohamed A. Alnakeeb; Mohaned M. El-Bashouty; Mostafa M. Zaytoun; Medhat M. Sorour (Case Studies in Thermal Engineering)
This numerical study examines the phase change material melting and solidification characteristics that are filled inside the shell of different multiple-tube arc array storage units. For all studied cases, the heat transfer surface area and the PCM quantities are kept constant. The melting and solidification are numerically simulated via the enthalpy-porosity method. A two-dimensional numerical model is created using the ANSYS-FLUENT 17.2 software. The current numerical model validation is achieved by comparing it with previously published study experimental data, demonstrating a strong agreement between the present model results and the earlier experimental findings. The results show that the arc location variation significantly influences both the melt and solidification. During the melting phase, the 180° arc array orientation showed the greatest reduction in total melting time, by 80.75 %, referred to the base case. In contrast, for the solidification phase period, the orientation of the 60° arc array demonstrated the most significant reduction in total solidification time, by 7.46 %, referred to the base case. For the full cyclic process, referred to the base case, the 90° arc array orientation obtained the greatest reduction for the total full cyclic time by 16.8 %.